Design and Implementation of an Arduino Uno Based Smart Automatic Water Dispenser Prototype - Muhammad Sakban; Purnama Helena Hutabarat (Jurnal Pepadun, 2026)
This study aims to design and develop an Arduino Uno–based smart automatic dispenser as a hygienic solution for touchless liquid dispensing. Conventional dispensers require physical contact, increasing the risk of contamination; therefore, a contactless system is proposed to improve hygiene and user convenience. The system utilizes an Arduino Uno as the main controller, an HC-SR04 ultrasonic sensor for object detection, a relay module for switching control, and a DC motor to pump liquid. A 16×2 LCD is integrated to display real-time system status. Experimental testing was conducted using repeated trials to evaluate detection accuracy, response time, and error rate. The results show that the ultrasonic sensor achieves 100% accuracy at 5 cm and approximately 95% at 10 cm, with decreased performance at longer distances. The DC motor and relay system demonstrated a 90% success rate with an average response time of 1.5 seconds. Overall system testing achieved 95% accuracy (19 out of 20 successful trials). These results indicate that the system operates effectively and reliably under defined conditions and has potential for application in public facilities to support hygienic and touchless liquid dispensing.